Biosynthesis of bimetallic silver–copper oxide nanoparticles using endophytic Clonostachys rosea ZMS36 and their biomedical applications - Chen, Zhijiang; Lv, Tianyu; Zhang, Yuxing; Kong, Weitao; Li, Xixian; Xie, Siyun; Li, Jiaqi; Long, Yu; Chen, Liqing; Liu, Jiarong; Li, Zhiqi; Zeng, Xingda; et al. (Frontiers in Microbiology, 2025)
Bimetallic nanoparticles (BMNPs) have garnered significant interest owing to their exceptional physicochemical properties. However, there have been few reports of the biosynthesis of BMNPs using endophytic fungi from medicinal plants. The objectives of this study were to isolate endophytic fungi from medicinal plant Anemarrhena asphodeloides to synthesize bimetallic Ag-CuO nanoparticles (Ag-CuO NPs), characterize the biosynthesized Ag-CuO NPs and assess their bioactivity and biosafety. The endophytic fungus ZMS36 capable of biosynthesizing Ag-CuO NPs was isolated from medicinal plant A. asphodeloides and identified as Clonostachys rosea. The Ag-CuO NPs were biosynthesized using endophytic C. rosea ZMS36 and characterized by UV-visible, SEM, TEM, EDS, XRD, and FTIR. The Ag-CuO NPs exhibited good antibacterial activity against Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Staphylococcus epidermidis, Salmonella typhimurium, and Shigella dysenteriae. They also significantly inhibited the growth of MRSA and the expression of mecA gene, especially in conjunction with vancomycin, the preferred antibiotic for clinical treatment of MRSA infections. The Ag-CuO NPs showed promising anticancer activity in antiproliferative assays on the tumor cell lines HeLa, PDSF, and A549. Furthermore, the Ag-CuO NPs inhibited the migration of HeLa cells as well as angiogenesis in chicken embryos, helping to inhibit tumor metastasis. Interestingly, the Ag-CuO NPs showed low cytotoxicity, indicating good biocompatibility. This study revealed the potential of endophytic fungi from medicinal plants to synthesize BMNPs and highlighted biosynthetic Ag-CuO NPs as promising novel antibacterial and anticancer nanodrugs for future biomedical applications.